Construction of R4 terms in N = 2 D = 8 superspace - Berkovits, Nathan [UNESP] (Elsevier B.V., 1998)
Using linearized superfields, R4 terms in the Type II superstring effective action compactified on T2 are constructed as integrals in N = 2 D = 8 superspace. The structure of these superspace integrals allows a simple proof of the R4 non-renormalization theorems which were first conjectured by Green and Gutperle. © 1998 Elsevier Science B.V.